Development of Light Box 3D Learning Media on IPAS Subject Material Properties of Light Class V Elementary School - Jumadiyah, Nabila; Zumrotun, Erna (Indonesian Journal of Primary Education, 2024)
The properties of light are one of the materials related to phenomena that often occur in the life of the living creatures. But in aligning the materials, learners are not shown anything tangible to clarify the material being studied. One way that can be done is to use a learning media namely Light Box 3D. This study aimed to measure the validity, practicality and effectiveness of learning media conducted on IPAS subject of light properties in class V SD Al-Islam Pengkol Jepara. Research and Development (R D) ) with ADDIE stage is the research method used in this study. The result of the media validation test showed a presentation of 92% with valid category, while the materials validation test showed a presentation 96%, which means that is very valid. The results of the media practicality test given to teachers and students showed the same average score of 96% which belongs to the category of very practical. The result of the effectiveness test performed showed a sig. (2-tailed) value of 0.0000.05, then H, is rejected and H, Is accepted. That is, there is a significant difference between the result of the pretest and posttest values performed. While the presentation of N-Gain value obtained was 76.9166% which belongs to the category of effective interpretation, thus it was conclude that the Light Box 3D Learning Media is very valid, practical and effectively to use